Analisis Kesejahteraan Karyawan pada PT P - Citra Ayu Isnina Alfi Wijayanti; Christian Wiradendi Wolor; Eka Dewi Utari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the impact of employee welfare on working conditions at PT P, focusing on welfare policies and facilities such as health insurance, employment insurance, on-site clinic services, maternity leave, workload balance, and working hours. Using a qualitative descriptive method, data were collected through interviews and direct observation of several employees. The findings show that company-provided welfare positively influences working conditions. Health facilities and work protection increase employees' sense of security and comfort. In addition, fair working hours, sufficient rest time, and attention to both physical and psychological well-being enhance work motivation and employee loyalty. Employees feel appreciated when the company supports work-life balance, leading to a more productive, harmonious, and low-conflict work environment. The study concludes that employee welfare is a key factor in shaping the quality of the workplace.